Techniques to correct and prevent acid mine drainage: a review (2014)
Acid mine drainage (AMD) from mining wastes is one of the current environmental problems in the field of mining pollution that requires most action measures. This term describes the drainage generated by natural oxidation of sulfide minerals when they are exposed to the combined action of water and atmospheric oxygen. AMD is characterized by acidic effluents with a high content of sulfate and heavy metal ions in solution, which can contaminate both groundwater and surface water. Minerals responsible for AMD generation are iron sulfides (pyrite, FeS2, and to a lesser extent pyrrhotite, Fe1-XS), which are stable and insoluble while not in contact with water and atmospheric oxygen. However, as a result of mining activities, both sulfides are exposed to oxidizing ambient conditions. In order to prevent AMD formation, a great number of extensive research studies have been devoted to the mechanisms of oxidation and its prevention. In this work, we present an explanation and theoretical valuation of the pyrite oxidation process and a compendium on the measures most frequently employed for its prevention and correction.